Sympathetic control on salivary secretion by the parotid gland in rabbit. I. Effects on the unstimulated gland (Revista Española de Fisiología, 1979)
The sympathetic influences on the rabbit unstimulated parotid gland were studied. The experiments were carried out in anaesthetized rabbits with the Stenon aduct cannulated. Direct stimulation of the superior cervical ganglion elicits variable salivary flows. The high amylase content in the saliva points to a sympathetic secretory action upon acinar cells. The administration of alpha-adrenergic blocking agents (dihydroergotamine, phentolamine and phenoxybenzamine) clearly reduces and even abolishes the effect of the sympathetic stimulation upon flow. The administration of a beta-adrenergic blocking agent (propranolol) slightly reduces the sympathetic action. However the amylase activity is greatly reduced. All this suggests that the secretory effects on the fluid fraction should predominantly be alpha-adrenergic while on the secretion of enzymes the beta-receptors should play an important role.